Acute lethal and sublethal effects of neem leaf extract on the neotropical freshwater fish Prochilodus lineatus - Winkaler, Elissandra U.; Santos, Thiago R. M.; Machado-Neto, Joaquim G.; Martinez, Claudia B. R. (Elsevier B.V., 2007)
The aim of this study was to determine the toxicity of the aqueous extract of neem leaves, a product extensively used in fish-farms as alternative for the control of fish parasites and fish fry predators, for the neotropical fish Prochilodus lineatus. The 24 It LC(50) of neem leaf extract for juveniles P lineatus was estimated as 4.8 g L(-1); the fish were then exposed for 24 h to 2.5, 5.0 and 7.5 g L(-1) or only clean water (control). Plasma glucose levels were higher in fish exposed to 2.5 g L(-1) and 5.0 g L(-1) neem extract, relative to control, indicating a typical stress response. Neem extract did not interfere with the osmoregulating capacity of the fish, as their plasma sodium, chloride, total protein and osmolarity did not change. The presence of the biopesticide interfered with the antioxidant defense system of P. lineatus, as there was a decrease in liver catalase activity at all neem concentrations and the detoxifying enzyme glutathione-S-transferase was activated in fish exposed to 5.0 g L(-1). Fish exposed to all neem extract concentrations exhibited damaged gill and kidney tissue. These results indicate that although neem extract is less toxic to P. lineatus than other synthetic insecticides used in fish-farming it does cause functional and morphological changes in this fish species. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acute toxicity; Azadirachta indica; biomarkers; Characidae